QUESTDONE APPLICATION WITH SOCIAL NETWORKING FEATURES AS THE ACTUAL WORLD INTERACTION MEDIA ON ANDROID SMARTPHONE - Rhio Sutoyo; Michael Yoshep; Andrew Susanto; Adrian Kurniadinata (Bina Nusantara University, 2012)
The purpose of this research is the design and implementation of an application that allows users to play and socialize at the same time and directly with the environment around the Android-based smart phone. This application is also expected to be a campaign media for a new product or specific event. The used method consists of two ways: the methods of analysis and design. The method of analysis includes the study of literatures, questionnaires, and comparisons with similar applications. The design method used for this research is Scrum. The obtained results are an application that helps users of Android-based smart phone to do social interaction and provide knowledge about the route that users will be addressed. It is also used as a new campaign media for entrepreneurs who want to promote a product or event. Furthermore, this application is also built with interesting but not complex design, thus allowing users to easily use it. The conclusions are this application provides experience for users to visit various places and can be a media campaign for a new product or specific event. It also becomes a tool of social interaction and useful for finding location of friends.Keywords: Applications; Social Networking; Interaction; Real World; Smartphone; Android